A study on Taiwan’s vocational senior high school teachers’ teaching identity and teaching transformation when facing a new competency-based curriculum - Lin, Tzu-Chien; Lee, Yi-Sang; Ye, Jian-Hong (Frontiers in Psychology, 2024)
Introduction The competency of education is advocated in the 2023 United Nations Sustainable Development Goals. UNESCO encourages countries to provide inclusive, equitable, competency education and lifelong learning opportunities for all. Starting from 2019, 12-Year-Basic-Education, a new curriculum, was fully implemented in Taiwan to conform to the competency education strategy. For the teachers on site, teachers’ understanding of the new curriculum and teaching practice has a direct impact on the competency of the implementation of this new policy. The main purpose of this study was to explore the relationship between vocational senior high school teachers’ competency-oriented teaching, teaching identity and teaching transformation regarding this new curriculum. Methods In order to effectively expand teachers’ understanding of competency-oriented teaching identity, this study put forward 6 hypothetical approaches based on the implicit theory of teaching transformation. The 747 valid questionnaires accounted for 97.1% of the total recovered questionnaires. The reliability and validity analyses, as well as overall model fitting analysis and research model validation were performed on these valid questionnaires. Results The results of the study showed: (1) With the background of Competency-oriented teaching, teachers’ teaching attitude and teaching willingness has a positive impact on teaching identity; (2) teachers’ teaching identity has a positive impact on teaching preparation, teaching practice, further study, three types of teaching transformation. In summary, three conclusions from this study were concluded on the aspects of teaching preparation, teaching practice and further study on practical competency-oriented teaching, teaching identity and teaching transformation in the educational field. Conclusion Three conclusions were derived for the relationships among these six constructs: (1) Teachers with a “good attitude” and “strong willingness” to teach, a “high sense of identification” acceptance and full implement of “teaching preparation” are considered as teachers with a “foresight and a visionary predictive style”; (2) Teachers with a high sense of self-awareness who can fully practice “teaching practice” are teachers with a “pragmatic teaching by example style”; (3) Teachers with a “good attitude,” a “strong willingness” to teach, a “high sense of identification” acceptance and who are able to fully practice “advanced research” are considered as teachers with an “empowerment-enhancing coaching style”.